Język religijny w badaniach filozoficznych, teologicznych i religioznawczych - Gajewska, Urszula (Słowo. Studia językoznawcze, 2012)
The present article provides the reader with the results of a survey on philosophical and theological concepts of religious language, its structure and characteristic features. Under consideration were taken three main trends in scientific researches: neopositivism (The Vienna Circle), functional and symbolic. Above that article discusses extremely important for linguistic reserches definitions of religious speeches, taken from the point of view of philosophy and theology: than revievs scientific stands on specific features of religious language like cognitive, instrumental, expressive and others. Presented both philosophical and theological reserches made influence on linguistic concepts of religious language.